God and necessity - Leftow, Brian, 1956- (Oxford University Press, 2012)
Brian Leftow offers a theist theory of necessity and possibility, and a new sort of argument for God's existence. He argues that necessities of logic and mathematics are determined by God's nature, but that it is events in God's mind - his imagination and choice - that account for necessary truths about concrete creatures.